Osmolality of donor human milk rises dramatically within minutes of fortification with varied degrees depending on the fortifier used - Tang, Qin; Yin, Dingding; Jin, Zhenchao; Zhang, Lian; Zhou, Ping (Frontiers in Pediatrics, 2025)
BackgroundThe addition of fortifiers to human milk can enhance its energy and protein content, although it results in an increase in osmolality, which may vary depending on the composition of fortifiers. The manner in which osmolality changes over time remains uncertain.AimsWe hypothesized that the impact of different fortifiers on osmolality would vary significantly and evolve dynamically with the duration of place time.MethodsOsmolality measurements were taken from the donor human milk (DHM)at 3 and 22 h after the addition of six different human milk fortifiers (HMFs) using a freezing osmolality meter. Furthermore, the osmolality was evaluated at nine time points following the standard fortification procedure with HMF1-3.Results(1) The mean osmolality of the unfortified donor milk was 299 mOsm/kg. The addition of three multi-component fortifiers (HMF1-3) led to a significant elevation in osmolality (P < 0.05), albeit to varying extents (54.6–109.1 mOsm/kg). The addition of the preterm formula HMF4 resulted in a lesser increase in osmolality in comparison to HMF1 and HMF2. (2) The osmolality increased significantly by 183.0 ± 27.4 mOsm/kg after the addition of the protein fortifier PF1, whereas it increased by only 8.9 ± 2.9 mOsm/kg after the addition of PF2 (P < 0.05). (3) The osmolality at 22 h showed a minimal increase of 0.3–3.7 mOsm/kg (0.1%–1.0%) compared to the osmolality at 3 h following the addition of the six fortifiers. (4) The increase in osmolality following fortification with HMF1-3 was predominantly observed within two minutes of addition, accounting for 85.9%–91.2% of the total increase, followed by a slow increase over the subsequent 12 h, with a slight decrease thereafter.ConclusionsThe addition of fortifiers significantly increased the osmolality of DHM. However, the degree of increase varied depending on the nutrient composition and content of the fortifiers used. It remains a challenge to avoid the rapid increase in osmolality of DHM within a very short time after the addition of a fortifier, even when fortifying at the bedside.